2021
DOI: 10.1039/d1ra00014d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of morphology on larvicidal activity of chemically synthesized zinc oxide nanoparticles against mosquito vectors

Abstract: We report the larvicidal impacts of four different morphologies of zinc oxide nanoparticles (ZnO NPs) [star-shaped (S), needle-like (N), plate-like (P), and cubical (C)] on mosquito larvae of Aedes albopictus and Anopheles vagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…An enhanced effect was imparted by AS-AgNCs compared to that of the AL-AgNCs. Similar effects, causing retarded growth of larvae, have been induced by the exposure of A. albopictus and A. vagus larvae to zinc oxide nanocomposites (ZnO-NCs), suggesting the delayed effects of the NCs ( Gunathilaka et al, 2021 ). Compared to the developmental duration in controls (8 days), they recorded an extended duration of 13 days (at LC 25 ), 14.67 days (at LC 50 ), 16.67 days (at LC 75 ), and 17 days (at LC 100 ), indicating the dose-dependent effects in the current study ( Gunathilaka et al, 2021 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…An enhanced effect was imparted by AS-AgNCs compared to that of the AL-AgNCs. Similar effects, causing retarded growth of larvae, have been induced by the exposure of A. albopictus and A. vagus larvae to zinc oxide nanocomposites (ZnO-NCs), suggesting the delayed effects of the NCs ( Gunathilaka et al, 2021 ). Compared to the developmental duration in controls (8 days), they recorded an extended duration of 13 days (at LC 25 ), 14.67 days (at LC 50 ), 16.67 days (at LC 75 ), and 17 days (at LC 100 ), indicating the dose-dependent effects in the current study ( Gunathilaka et al, 2021 ).…”
Section: Discussionmentioning
confidence: 88%
“…Similar effects, causing retarded growth of larvae, have been induced by the exposure of A. albopictus and A. vagus larvae to zinc oxide nanocomposites (ZnO-NCs), suggesting the delayed effects of the NCs ( Gunathilaka et al, 2021 ). Compared to the developmental duration in controls (8 days), they recorded an extended duration of 13 days (at LC 25 ), 14.67 days (at LC 50 ), 16.67 days (at LC 75 ), and 17 days (at LC 100 ), indicating the dose-dependent effects in the current study ( Gunathilaka et al, 2021 ). Nevertheless, the effect of phytomediated nanocomposites has not been assessed as the modifiers of larval behavior although several studies have documented behavioral alterations in mosquito larvae on exposure to the plant extracts, revealing restlessness, excitation, coiling movements, and formation of a ring-like structure.…”
Section: Discussionmentioning
confidence: 88%
“…The toxicity of nanoparticles on mosquito larvae can be attributed to their efficacy to penetrate through the insect’s cuticle and, thereby, block the respiratory openings on the skin followed by suffocation and, ultimately, death . Upon ZnO nanoparticles penetrating into the cuticle, it can induce morphological changes on the hemocytes upon exposure, thereby leading to deformations and decrease in their viability. , Additionally, the toxicity of ZnO nanoparticles to insects can be related to their ability to induce ROS and, thereby, cause the liberation of toxic ions inside the insect’s cells. , Another larvicidal mechanism of ZnO nanoparticles can be related to their surface defects for a different texture . These surface defects, especially at the corners and edges, can be abrasive and can damage the larva cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of that study revealed that the silver nanoparticles demonstrated significant effectiveness against both mosquito species at different developmental stages (Fouad et al, 2018). Gunathilaka et al (2021) observed that the development rate of surviving mosquito larvae was delayed when exposed to ZnO nanoparticles, indicating their potential to both kill and inhibit the growth of Aedes albopictus and Anopheles vagus larvae. The mode of action of Fe-MOF nanoparticles on Cx.…”
Section: Discussionmentioning
confidence: 99%